Non‐Vitamin K Antagonist Oral Anticoagulants Provide Less Adverse Renal Outcomes Than Warfarin In Non‐Valvular Atrial Fibrillation: A Systematic Review and MetaAnalysis - Sitticharoenchai, Patita (J Am Heart Assoc, 2021)
BACKGROUND: Non‐vitamin K antagonist oral anticoagulants (NOACs) have better pharmacologic properties than warfarin and are recommended in preference to warfarin in most patients with non‐valvular atrial fibrillation. Besides lower bleeding complications, other advantages of NOACs over warfarin particularly renal outcomes remain inconclusive. METHODS AND RESULTS: Electronic searches were conducted through Medline, Scopus, Cochrane Library databases, and ClinicalTrial.gov. Randomized controlled trials and observational cohort studies reporting incidence rates and hazard ratio (HR) of renal outcomes (including acute kidney injury, worsening renal function, doubling serum creatinine, and end‐stage renal disease) were selected. The random‐effects model was used to calculate pooled incidence and HR with 95% CI. Eighteen studies were included. A total of 285 201 patients were enrolled, 118 863 patients with warfarin and 166 338 patients with NOACs. The NOACs group yielded lower incidence rates of all renal outcomes when compared with the warfarin group. Patients treated with NOACs showed significantly lower HR of risk of acute kidney injury (HR, 0.70, 95% CI, 0.64–0.76; P<0.001), worsening renal function (HR, 0.83; 95% CI, 0.73–0.95; P=0.006), doubling serum creatinine (HR, 0.58; 95% CI, 0.41–0.82; P=0.002), and end‐stage renal disease (HR, 0.82; 95% CI, 0.78–0.86; P<0.001). CONCLUSIONS: In non‐valvular atrial fibrillation, patients treated with NOACs have a lower risk of both acute kidney injury and end‐stage renal disease when compared with warfarin.